Clinical profile of patients with forearm and hand injuries - Bisht, Bhaskar; Rajan, Manu; Dvivedi, Sanjay; A. V. Rawat, Kinnari; Konda, Sireesha (International Surgery Journal, 2020)
Background: Hand injuries are among the most frequent injuries, constituting between 6.6% and 28.6% of all injuries. Hand and forearm injuries, however small or large they may be do have a significant impact on the society in terms of cost of treatment, hospital stay and costs of lost production and hence the importance of this study. Methods: The study was conducted in the Department of Surgery, Himalayan Institute of Medical Sciences (HIMS), Swami Ram Nagar, Dehradun, over the period of 12 months. Subjects were recruited from patients presenting in emergency/surgery OPD, HIMS, Dehradun with a primary diagnosis of soft tissue injuries in the forearm and the hand. A total of 114 patients were included in the study. Results: Overall mean age of the subjects in our study was 28.21±15.71. The highest incidence was in the age group of (20-40) years i.e. 62 (54.30%). Male to female ratio in our study was 6.6:1. Maximum injuries occurred as workplace and industrial injuries. This contributed to 34.2% (39 subjects) of overall injuries. 50% patients had crush injuries while lacerations, burn and avulsion were other form of injuries. 43 patients had bone and joint involvement,16 patients had neurovascular injuries and 20 patients had tendon injuries. Conclusions: Hand and forearm injuries are more common in males and in the age group of 20 to 40 years leading to loss of productive working days causing a significant financial burden on the society.